Effect of swimming and asthmatic exercise on forced expiratory volume in 1 second (FEV1) and levels of cortisol hormone in asthmatics patients - Achmad Djunaedi, Rahmaya Nova Handayani, Denny Agustiningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Bronchial asthma is one of the allergic diseases characterized by reversible bronchial narrowing dueto bronchial hyperactivity and obstruction of respiratory tract. The prevalence and hospitalizationrates of bronchial asthma keep increasing from year to year, causing asthma to be the top ten causesof morbidity and mortality in Indonesia. The decrease of the forced expiratory volume in 1 second(FEV1) is one of the indicators of the respiratory tract obstruction. Moreover, the cortisol hormonelevel is also associated with asthma. Asthma can be treated not only with pharmacological interventionbut also physical exercises. The aim of the study was to assess the increase of FEV1 and cortisolhormone level after swimming and asthmatic exercise on asthmatic patients. This was a quasiexperimental study using pre and post test control group design. Two groups of 10 asthmaticpatients each conducted swimming and asthmatic exercise as intervention. On pre, middle and postswimming or asthmatic exercise, those two groups underwent the measurement of FEV1 using aspirometer and cortisol hormone levels using ELISA methods. The result showed that the value ofFEV1 and cortisol hormone levels increased significantly after swimming and asthmatic exercise(p<0.05). Moreover, the improvement of FEV1 value and cortisol hormone levels of asthmaticpatients in swimming were higher than asthmatic exercise. In conclusion, swimming and asthmaticexercise can increase the value of FEV1 and the levels of the cortisol hormone.Keywords : swimming - asthmatic exercise - FEV1 - cortisol hormone - asthma